Isolation and Molecular Weight Characterization of Tetragonula laeviceps Honey Protein - Sahlan, Muhamad; Azizah, Nurul; Hakamada, Kazuaki; Noguchi, Keiichi; Yohda, Masafumi (Makara Journal of Technology, 2018)
The concentration of protein in honey is lower than polysaccharide. However, recently the honey’s protein is intensively studied and it showed that protein also have several biological activities such as antibacterial activity. The purpose of this research is to isolate and characterize Tetragonula laeviceps honey protein by determining the molecular weight. Honey protein of Trigona laeviceps was isolated using ultra-filtration with the membrane’s size of 30 kDa, then concentrated using tube membrane size 10 kDa. Molecular weight was analyzed by SDS PAGE. From the analysis, there was major protein band in honey produced by Tetragona laeviceps identified. The produced molecular weight of major protein bands were about 87 and 65 kDa. Determining of the molecular weight of this protein could be used to detect the originality of Tetragonula laeviceps honey from Indonesia.